In Vivo miRNA Decoy Screen Reveals miR-124a as a Suppressor of Melanoma Metastasis - Moubarak, Rana S.; Koetz-Ploch, Lisa; Mullokandov, Gavriel; Gaziel, Avital; de Pablos-Aragoneses, Ana; Argibay, Diana; Kleffman, Kevin; Sokolova, Elena; Berwick, Marianne; Thomas, Nancy E.; Osman, Iman; Brown, Brian D.; et al. (Frontiers in Oncology, 2022)
Melanoma is a highly prevalent cancer with increasing incidence worldwide and high metastatic potential. Brain metastasis is a major complication of the disease, as more than 50% of metastatic melanoma patients eventually develop intracranial disease. MicroRNAs have been found to play an important role in the tumorigenicity of different cancers and have potential as markers of disease outcome. Identification of relevant miRNAs have generally stemmed from miRNA profiling studies of cells or tissues, but these approaches may have missed miRNAs with relevant functions that are expressed in sub-fractions of cancer cells. We performed an unbiased in vivo screen to identify miRNAs with potential functions as metastasis suppressors using a lentiviral library of miRNA decoys. Notably, we found that a significant fraction of melanomas that metastasized to the brain carried a decoy for miR-124a, a miRNA that is highly expressed in the brain/neurons. Additional loss and gain-of-function in vivo validation studies confirmed miR-124a as a suppressor of melanoma metastasis, and particularly of brain metastasis. miR-124a overexpression did not inhibit tumor growth in vivo, underscoring that miR-124a specifically controls processes required for melanoma metastatic growth, such as seeding and growth post-extravasation. Finally, we provide proof-of-principle of this miRNA as a promising therapeutic agent by showing its ability to impair metastatic growth of melanoma cells seeded in distal organs. Our efforts shed light on miR-124a as an anti-metastatic agent, which could be leveraged therapeutically to impair metastatic growth and improve patient survival.